AB0244 MIR-155 Expression in B Cells of Rheumatoid Arthritis Patients Is Related To Follicular Synovitis and Mirrors B Cell Subpopulations Changes after IL-6R Inhibitor Treatment. (15th July 2016) - Alivernini, S.; Tolusso, B.; Petricca, L.; Kurowska-Stolarska, M.; Fedele, A.L.; Gremese, E.; Di Sante, G.; McInnes, I.B.; Ferraccioli, G.
Abstract : Background: MicroRNA-155 (miR-155) was shown to be a key regulator of B cell biology. The fine-tuning of the transcription factor PU.1 by miR-155 is required for high-affinity IgG1 production and B cell maturation. However, the role of miR-155 in the activation of B cells in Rheumatoid Arthritis (RA) has not been explored. Objectives: To investigate miR-155 expression in RA B cells and its association with B cell subpopulations distribution, synovial histological pattern and anti-IL6R treatment response. Methods: 42 RA patients naive to treatment who underwent synovial tissue (ST) biopsy were enrolled and 30 RA no responder to MTX (MTX-IR) and 15 Osteoarthritis (OA) patients were used as comparison. Based on immunostaining for CD68, CD21, CD3 and CD20 cells, ST samples were categorized as diffuse or follicular pattern. CD19+ cells were isolated from peripheral blood (PB) and B cells subpopulations were assessed by FACS using IgD/CD27 classification. In 14 MTX-IR ERA patients starting TCZ (8 mg/kg), PB-derived CD19+ cells were tested for B cells subpopulations at baseline and after 3–6 and 12 months in association with miR-155 and PU.1 expression by qPCR. IL-6 receptor (IL6-R) was experimentally confirmed as miR-155 target by Luciferase assay. PB-derived CD19+ cells of HC were stimulated with IL-6 (20 pg/mL) and miR-155 expression was checked after 24–48 and 72h respectively. Results: At study entry, naive RA and MTX-IR patients showed higher incidence of follicular synovitis than OA patients (p=0.001 and p=0.002 respectively). Moreover, RA patients with follicular synovitis were more likely ACPA positive (p=0.001) compared to patients with diffuse pattern. At baseline, PB derived B cells of RA patients were characterized by higher IgD – CD27 – cells (p=0.05) percentages compared to HC. Moreover, PB-derived CD19+ cells of RA patients with follicular synovitis showed an activated memory phenotype compared to patients with diffuse pattern (p=0.01). Finally, PB-derived CD19+ cells of naive and MTX-IR RA patients with follicular synovitis showed significantly higher expression of miR-155 compared to HC (p=0.001 and p=0.002 respectively) mainly in ACPA positive patients (p=0.001). During IL-6R inhibitor treatment, we found that IgD – CD27 – cells percentage significantly decreases after 12 months (p<0.05) follow-up compared to baseline. miR-155 expression in PB-derived CD19+ cells was significantly down-regulated after 3 (p=0.01), 6 (p=0.002) and 12 (p=0.001) months of TCZ treatment respectively. Conversely, PU.1 expression in PB-derived CD19+ cells was significantly up-regulated after 12 months (p=0.04) of TCZ treatment. Finally, miR-155 was found to be an inducible miR after IL-6 stimulation (p<0.05). Conclusions: B-cells of naïve and MTX-IR RA patients with follicular synovitis show a memory phenotype and a high expression of miR-155 which is related with ACPA positivity. Moreover, miR-155 expression in PB-derived B cells of RA patients significantly decreases during IL-6R inhibitor treatment mirroring the changes of B cell subpopulations distribution. Thus, miR-155 may represent a key regulator of B-cells in RA through IL-6 pathway. Disclosure of Interest: None declared